'You can't really define it can you?' Rangatahi perspectives on hauora and wellbeing. Issue 4 (8th August 2022) - Carlson, Teah; Calder-Dawe, Octavia; Jensen-Lesatele, Victoria
ABSTRACT: A sustained national focus on improving youth mental health and wellbeing in Aotearoa is strongly indicated by current national prevalence statistics. Wellbeing is, however, complex and situated, as well as notoriously difficult to define and operationalise. To facilitate good lives for young people, we need to enrich our conceptualisations of what wellbeing means and how it unfolds for diverse rangatahi, in context. In this paper, we share findings from an in-depth, collaborative qualitative research project exploring rangatahi hauora. A central purpose of our work has been to find ways to enliven and challenge existing discourse on youth wellbeing with the voices and perspectives of diverse young people. Drawing from open-ended interviews conducted with 56 culturally diverse rangatahi (young people) aged 16–20 living in Tāmaki Makaurau (Auckland), we present a layered analysis of rangatahi's hauora narratives, framed around the concept of whakawhanaungatanga . Our analysis attends to the centrality of connection and relationships in rangatahi's talk and explores resonances and dissonances with other culturally available sources of knowledge about young people. Our paper concludes by briefly considering the implications of our analysis and their potential to advance and diversify existing understandings of rangatahi hauora in Aotearoa.